1998
DOI: 10.1074/jbc.273.19.11937
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Characterization of a Conditionally Active Version of the Serine/Threonine Kinase Akt

Abstract: Akt is a serine/threonine kinase that requires a functional phosphatidylinositol 3-kinase to be stimulated by insulin and other growth factors. When directed to membranes by the addition of a src myristoylation sequence, Akt becomes constitutively active. In the present study, a conditionally active version of Akt was constructed by fusing the Akt containing the myristoylation sequence to the hormone binding domain of a mutant murine estrogen receptor that selectively binds 4-hydroxytamoxifen. The chimeric pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
259
2
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(274 citation statements)
references
References 36 publications
11
259
2
2
Order By: Relevance
“…As also shown in Fig. 2A, in F/B* cells (as in other cells transfected with constitutively active PKB (8,37,38)), p70S6 kinase was activated, evidenced by the shift in its mobility on SDS-PAGE. Rapamycin blocked activation of p70S6 kinase without affecting PKB or PDE3B activity, but did reduce PDE4 activity, which was slightly increased in F/B* cells (Table I; Fig.…”
Section: Role Of Pkb In Igf-i-induced Activation Of Pde3b In Fdcp2 Cellsmentioning
confidence: 78%
See 1 more Smart Citation
“…As also shown in Fig. 2A, in F/B* cells (as in other cells transfected with constitutively active PKB (8,37,38)), p70S6 kinase was activated, evidenced by the shift in its mobility on SDS-PAGE. Rapamycin blocked activation of p70S6 kinase without affecting PKB or PDE3B activity, but did reduce PDE4 activity, which was slightly increased in F/B* cells (Table I; Fig.…”
Section: Role Of Pkb In Igf-i-induced Activation Of Pde3b In Fdcp2 Cellsmentioning
confidence: 78%
“…4), wortmannin could inhibit constitutively activated PKB by blocking production of phosphoinositides involved in PKB association with membranes and/or in the activation of specific PDK isoforms. Whether activated PKB contributes to feedback activation of PI3-K or sensitization of PDK to phosphoinositides is not known, but other workers have also reported that wortmannin or LY294002 inhibits constitutively activated PKB (activated by targeting to membranes) in 3T3-L1 adipocytes (38) or HEK293 cells (37).…”
Section: Role Of Pkb In Phosphorylation/activation Of Pde3b In Fdcp2 mentioning
confidence: 99%
“…To analyse the effects of Akt signaling activation on epidermal cells, we used a chimeric protein composed of a myristoylated constitutively active form of Akt and the ligand-binding domain of a mutant estrogen receptor (Mer) (Kohn et al, 1998). The fusion protein can control the timing and duration of Akt signaling activation because Akt-Mer is inactivated in the absence of 4-hydroxytamoxifen (4OHT), but activated rapidly by the addition of 4OHT (Watanabe et al, 2006).…”
Section: Generating Akt-mer Transgenic Micementioning
confidence: 99%
“…The PI3-K promotes the catalysis of the inositol ring of phosphoinositides at position 3 resulting in (3,4,5) phosphatidylinositol triphosphate (PIP3) from (4,5) phosphatidylinositol biphosphate (Cavalheira et al 2002, van Dam et al 2005. PIP3 provides the phosphorylation of phosphoinositidedependent protein kinase 1 (PDK1) which in turn activates protein kinase B (PKB) or AKT (Kohn et al 1998) and protein kinase C (PKC) (Shepherd and Kahn 1999). Following its recruitment to the cell surface, AKT is activated resulting in the AKTdependent phosphorylation of many substrates.…”
Section: Insulin-dependent Pathwaymentioning
confidence: 99%